Os fundamentos teóricos da resolução privada de conflitos: as implicações jusfilosóficas do conceito de sociabilidade humana entre o contratualismo clássico e o iluminismo escocês - Diógenes, George Lucas Souza (2020)
This inquiry aims at analysing and clarifying the relation between the concept of human sociability and the conflict management structure – which is meant here as the set of methods, people, institutions and mechanisms regarded as fit for the prevention and resolution of conflicts of interest – in the Classical Contractualism, represented by the work of Thomas Hobbes, JeanJacques Rousseau and John Locke, and in the Scottish Enlightenment through the philosophy of Francis Hutcheson, Adam Ferguson and David Hume. In both cases, the underlying theories of knowledge by each author serve as this survey’s main source. The methodology employed in this theoretical investigation consists of a descriptive, comparative and critical approach, backed by bibliographical research, which arrived at the conclusion that the notion of an original human sociability reveals itself as the theorical basis for the decentralization of the conflict management structure. This relation rests ultimately on the opposition brought about by the voluntarism and the classical philosophy's heritage, so that human nature’s broadening through the addition of non-volitive attributes contributes to shape the basis of the juridical order, as well as its limits and its decentralization